Leadership styles in the Ecuadorian public media - Londoño-Proaño, Cristián (2022)
The digital transformation generated vertiginous and important changes in the media industry. There is content saturation and variation in the consumption pattern. Audiences migrated from traditional to digital media. Several were sold, while others were merged. New actors are inserted every day, increasing the competition from the media. Leadership, innovation, and creativity are some of the alternatives that the media can use to seize opportunities and become competitive. Transformational leadership is a style used in the communication industry sector, due to the same fact that in the newsroom (or production) it is necessary for leaders to have a behavior that favors creativity and innovation, in order to be more competitive. In this research, the Multifactor Leadership Questionnaire - MLQ-5X instrument is used, which is a widely used tool to measure leadership. It is possible to establish that, in the public media, transformational leadership is the predominant style, that there is a considerable and positive correlation between idealized behavioral influence, intellectual stimulation and motivation and inspiration with satisfaction and effectiveness. Communication professionals from Public Media perceive that directors, bosses, and coordinators are leaders who motivate and inspire others to accomplish goals, they can even give more of themselves thanks to their engagement and trust.